THE COMPETENCE AND MOTIVATION RELATIONSHIP WITH TEACHER PERFORMANCE AT STATE VOCATIONAL SCHOOL 4 KABUPATEN KAUR - Leza Kurniati; Ida Anggriani; Abdul Rahman (Penerbit Jurnal Indonesia, 2020)
The research aim to know the relationship of competence and motivation with performance teacher at SMK Negeri 4 Kaur Regency. Method Analysis the used is correlation spearman rank and hypothesis test. From result of calculation of correlation of rank spearman between competence with performance teacher at SMK Negeri 4 Kaur Regency known by value of rho count equal to 0,812 its meaning the relationship of competence with performance teacher at SMK Negeri 4 Kaur Regency is very strength, because correlation value reside in coefficient interval 0,800 - 1,000. From result of calculation of correlation of rank spearman between motivation with performance teacher at SMK Negeri 4 Kaur Regency known by value of rho count equal to 0,665 its meaning of the relationship motivation with performance teacher at SMK Negeri 4 Kaur Regency is strength, because correlation value reside in coefficient interval 0,600 - 0,799. Assess rho count for the relationship competence with performance teacher at SMK Negeri 4 Kaur Regency equal to 0,812 while rho tables is 0,392 or 0,812 > 0,392 so that Ho refused and Ha accepted, its meaning there are relation which is significant between competence with performance teacher at SMK Negeri 4 Kaur Regency. While Assess rho count for the relationship motivation with performance teacher at SMK Negeri 4 Kaur Regency equal to 0,665 while rho tables is 0,392 or 0,665 > 0,392 so that Ho refused and Ha accepted, its meaning there are relation which is significant between motivation with performance teacher at SMK Negeri 4 Kaur Regency.